Feminism Study of the Novel “Catatan Juang” by Fiersa Besari - Marfuah Laswaniyah (CV. Tripe Konsultan, 2021)
This study aims to explain the feminism of the Suar character in the novel “Catatan Juang” by Fiersa Besari in terms of liberalist feminism and post-modern feminism. This research method is a qualitative descriptive method. The source of data in this research is the novel